PENDEKATAN ISLAM RASIONAL: Kajian Atas Pemikiran Islam Muhammad Abduh - Wafda Muhammad; Fadil (Salimiya: Jurnal Studi Ilmu Keagamaan Islam, 2024)
This article examines the rational Islamic thought of Muhammad Abduh, a prominent 19th-century Muslim scholar. The method used in this article is a literature review approach, using relevant literature as research material and sources. The result of this research is that Abduh offered an Islamic approach that emphasizes rational understanding, criticism, and modernization in interpreting Islamic teachings. Abduh argued that Islam is compatible with reason and scientific advancement, rejecting blind adherence (taqlid) and encouraging Muslims to perform ijtihad in understanding sacred texts. He emphasized the importance of reforming Islamic thought to address contemporary challenges. This article explains Abduh's ideas on educational reform, Qur'anic interpretation, and the role of reason in understanding Islamic teachings. A critical analysis of Abduh's thoughts is also presented to assess his contributions and limitations in contemporary Islamic thought discourse.